Inventarisasi dan Studi Komposisi Capung (Odonata) pada Area Persawahan Kelurahan Warugunung, Surabaya, Jawa Timur - Muhamad Azmi Dwi Susanto; Najwa Maulidina Putri (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
The rice field area of ​​Warugunung Village is an agricultural area with a pond. In rice fields there are various kinds of insects and ponds which are aquatic habitat types with great potential as natural habitats for dragonflies (Odonata). Dragonflies are flying insects that have an important role in the ecosystem, namely maintaining the balance of the food chain by being a predator for insect pests. This study aims to inventory and determine the composition of dragonflies found in the rice fields of Warugunung Village, Surabaya. The research method used is the VES (Visual Ecounter Survey) method and belt transects, as well as data analysis using the Shannon-Wienner (H') species diversity index formula. The results obtained were 17 species from 3 families with a total of 139 individuals. The results of the diversity index analysis show that the lowest diversity index is found at the Vegetation Pond observation location with a value of H'= 2.41 and the lowest diversity index is at the rice field observation location with a value of H'= 1.27.